Validity and reliability of the knowledge and attitude assessment tool for cadres in tsunami-prone areas - Ekaputri, Kintan Resqitha; Faizatiwahida, Novia; Andini, Febri Tri; Oktaria, Rina; Mukhlis, Zikri; Nasution, Riska Amalya; Sari, Putri Irwanti (PT. Mega Science Indonesia, 2025)
Padang city is a high-risk area for tsunamis, making the presence of disaster preparedness cadres crucial as the frontline in response. However, many cadres have never received formal training and have limited knowledge and attitudes regarding tsunami emergencies. Cadre competency evaluation has been hampered by the lack of specific, psychometrically tested instruments. This study aimed to test the validity and reliability of tsunami preparedness knowledge and attitudes instruments for cadres in tsunami-prone areas. This cross-sectional study included 90 respondents. The instrument was developed through a literature review and a qualitative study. Content validity was tested through expert assessment via three expert judgments. The construct validity and reliability were tested on 90 cadres. Instrument validity was assessed via biserial correlation (knowledge) and Pearson’s product‒moment correlation (attitude). Reliability was tested via the Kuder Richardson formula (KR-20) and Cronbach's alpha. The results of the expert judgments on the knowledge and attitude questionnaires were 0.81–1 and 0.75–1, respectively. The construct validity test resulted in 12 knowledge statement items and 12 attitude items that were declared valid, with R values > R values. The reliability test results for the knowledge and attitude questionnaires were 0.630 and 0.737, respectively, indicating that the questionnaire is reliable. This instrument can be used by health workers, community nurses, and policymakers to map cadre capacity accurately and as an evaluation tool before and after providing future disaster training